Genus Alga pada Lahan Sawah Organik yang Ditanami Padi Lokal dan Inhibrida di Subak Jatiluwih, Tabanan - SAWIDYA FITRIYANI; I WAYAN DANA ATMAJA; NI NENGAH SONIARI (Fakultas Pertanian Universitas Udayana, 2019)
Algae Genus in Organic Rice Fields Planted with Local and Inhibrida Rice in Subak Jatiluwih, Tabanan. The abundance of microalgae in rice fields, especially microalgae from Cyanophyta division that are capable of fixing nitrogen, is very important helping maintain soil fertility. The aim of this study was to find out the genus of algae in organic rice fields of Subak Jatiluwih, Tabanan. The research was conducted from September 2018 to April 2019. Sampling was done in Subak Jatiluwih. Algae breeding were carried out at Biology and Physics Laboratory, Faculty of Agriculture, Udayana University. This research method uses descriptive quantitative. The implementation of the research included the determination of location, soil and water sampling, identification of algae, and analysis of algae genera. Enrichment algae was carried out using the MPN method, results of the analysis of algae genus were found in 37 genera from 3 divisions i.e Chlorophyta, Cyanophyta and Chrysophyta. Descriptive quantitative method Most Probable Number (MPN) calculation conclude that there are not much different from the Local and Inhibrida rice fields. The maximum population algae of local rice fields is 1.100 cell g-1 and Inhibrida rice fields is >1.100 cell g-1 of land. The minimum population is 3,6 cell g-1 of land in local rice fields, and 9,2 cell g-1 of land in Inhibrida rice fields.